Pengaruh Pengangguran dan Inflasi Terhadap Tingkat Kemiskinan di Indonesia Pada Tahun 2015-2023 - Puteri, Adinda Afrilia; Wildatussilmiah, Okti; Yunani, Yunani; Harning, Rekhiannisa Dwi; Dermawan, Deris (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
The problem of poverty is not only a challenge for developing countries like Indonesia, but is also a major concern for many countries throughout the world. Even though Indonesia has succeeded in reducing the poverty rate, in reality there are still many people in various provinces, especially in the Eastern Region of Indonesia (KTI), who live below the poverty line. Efforts to overcome this problem are very important for the welfare of the people in the region. The main aim of this research is to analyze the relationship between unemployment and inflation rates and poverty rates. The method used is a quantitative method, with data obtained from the Central Statistics Agency to describe the phenomenon of unemployment and inflation. The result is that unemployment does not have a significant and negative influence on poverty. However, inflation has a negative and significant influence on poverty. Simultaneously, unemployment and inflation do not have a significant and negative impact on poverty.